Computing Tools for Implementing Standards for Single-Case Designs. (November 2015) - Chen, Li-Ting; Peng, Chao-Ying Joanne; Chen, Ming-E
In the single-case design (SCD) literature, five sets of standards have been formulated and distinguished: design standards, assessment standards, analysis standards, reporting standards, and research synthesis standards. This article reviews computing tools that can assist researchers and practitioners in meeting the analysis standards recommended by the What Works Clearinghouse: Procedures and Standards Handbook —the WWC standards. These tools consist of specialized web-based calculators or downloadable software for SCD data, and algorithms or programs written in Excel, SAS procedures, SPSS commands/Macros, or the R programming language. We aligned these tools with the WWC standards and evaluated them for accuracy and treatment of missing data, using two published data sets. All tools were tested to be accurate. When missing data were present, most tools either gave an error message or conducted analysis based on the available data. Only one program used a single imputation method. This article concludes with suggestions for an inclusive computing tool or environment, additional research on the treatment of missing data, and reasonable and flexible interpretations of the WWC standards.